KAJIAN INFRASTRUKTUR PASAR TRADISIONAL NAGARI TANJUNG GADANG KECAMATAN TANJUNG GADANG KABUPATEN SIJUNJUNG - Sari, Mira Mayang (STKIP PGRI Sumbar, 2014)
This study aims to determine infrastructure assessment traditional market village Tanjung Gadang sub district Tanjung Gadang district sijunjung. This type of research is descriptive. population in this study are all traders in traditional markets village Tanjung Gadang sub district Tanjung Gadang district sijunjung consisting of merchants and traders los overhang. The sample of respondents was taken with proportional random sampling technique with the proportion of 15%, totaling 70 samples. analysis techniques to the analysis of data using a percentage formula. techniques of data collection through questionnaires. of the results of the study found that: 1) overhang traders who sell in the traditional market village of Tanjung Gadang and its relationship to the street, that the market contained in the Tanjung Gadang running smoothly and do not disrupt the activities of buying and selling (57.15%). Stores located in Tanjung traditional market Gadang, he has a good shop (74.29%), it feels good market yard (47.15%), open fields in traditional Tanjung Gadang not bring barriers (65.71%) , Tables existing in traditional Tanjung Gadang has no effect on the sale of the merchant (47.14%), and mats available in the market Tanjung Gadang made of fine materials (87.15%), building on the market are made of traditional Tanjung Gadang of sand that many (62.85%), and the latter of which manages the Tanjung Gadang is the traditional market of individuals (70%). 2) Los existing Tanjung Traditional Market Gadang building in traditional Tanjung los Gadang, the building regularly (51.43%), large size is less (62.86%), los (45.72%), and who manage los in traditional Tanjung Gadang is the clerk of the market (82.86%), the location of the Tanjung traditional market los Gadang adequate (51.43%), the number of traditional markets Tanjung los Gadang 9 units (84.29%), and materials for building los are made of quality materials (82.85%), and the last of the rent payments in traditional Tanjung Gadang los, los rental paid to the clerk of the market (84.29%). 3) WC, materials to build latrines in traditional markets Tanjung Gadang, made of material less good (41.43%), Air WC in traditional markets Tanjung Gadang, clean water (41.43%), distance from places selling lavatory the traditional market is much Tanjung Gadang (50%), WC conditions that exist in traditional markets Tanjung Gadang is less clean (44.29%), and the managing WC in traditional Tanjung Gadang is the clerk of the market (74.29%), number of WC contained in traditional markets Tanjung Gadang 2 pieces (61.42%), and the latter about lighting, lighting in traditional Tanjung WC Gadang, his WC not have lighting (37.15%).